1999
DOI: 10.2136/sssaj1999.6341013x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Physical Organic Matter Fractions During De‐inking Sludge Decomposition

Abstract: Replenishment of soil C and N is essential for sustainable revegetation of minesoils. Our study investigated paper de‐inking sludge as the organic amendment for revegetating an abandoned sandpit in Québec, Canada. Sludge was incorporated at 0 (check) and 105 Mg dry matter ha−1 before seeding tall wheatgrass (Agropyron elongatum (Host) Beauv.). Nitrogen (at 315, 630 and 945 kg N ha−1) and P (at 52.5 and 105 kg P ha−1) were also applied to all plots. Distribution of C and N was determined periodically in two siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…In fact, only a trend (not shown) was noticed as slightly more material (~ 6% of initial amount) remained with the highest N application rate. However, measurements of whole soil and particulate C confirmed the positive effect of N on C conservation in the same study (Fierro et al, 1999c) Nitrogen immobilization was expected to be substantial in the early stages of decomposition, because of the high initial C/N ratio of sludge. Supplemental N was forethought to compensate for immobilization while allowing vegetation establishment.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In fact, only a trend (not shown) was noticed as slightly more material (~ 6% of initial amount) remained with the highest N application rate. However, measurements of whole soil and particulate C confirmed the positive effect of N on C conservation in the same study (Fierro et al, 1999c) Nitrogen immobilization was expected to be substantial in the early stages of decomposition, because of the high initial C/N ratio of sludge. Supplemental N was forethought to compensate for immobilization while allowing vegetation establishment.…”
Section: Discussionsupporting
confidence: 68%
“…However, Fierro et al (1999c) have confirmed the slow decomposition of this material based on whole-soil C and physical fraction measurements.…”
Section: Discussionmentioning
confidence: 65%
“…Chantigny et al (1999) reported that 60% of the total C from a primary de-inking sludge was oxidised in 2 yr. This decomposition rate from primary de-inking sludge also varies with N supply (Fierro et al 1999). Heavy metals (Cd, Co, Cr, Cu, Mn, Ni, Pb, and Zn) were present in low concentrations (Table 3) except for Mn and respected the "A" criteria for PS application to edible crops (Ministère de l'Environnement et de la Faune du Québec 1997).…”
Section: Sludge Compositionmentioning
confidence: 99%
“…This suggests that a large part of the organic N was in very labile forms or that the sludge helped to conserve soil N. It was reported that primary deinking sludge additions to soil helps to conserve N (Fierro et al 1999), which can in part be re-mineralised the following year (Simard et al 1998a).…”
Section: Winter Cabbage Yieldmentioning
confidence: 99%
“…We discussed this point in our paper and referred to Fierro et al (1999c) in which physical fractionation was used to characterise the remaining material. Chantigny et al (2000) used wet chemistry (carbohydrate analysis) to study DPS decomposition in an arable soil.…”
Section: Specific Commentsmentioning
confidence: 99%